Does Asthma Affect the Risk of Developing Breast Cancer? - Karin B. Michels; Orianne Dumas; Raphaelle Varraso; Carlos A. Camargo Jr (Cancer Medicine)
ABSTRACT Background The role of the immune system in cancer defense is likely underappreciated. While there has been longstanding interest in the role of atopic diseases in cancer, only a few studies have tested this hypothesis. Methods We analyzed data from 202,055 women participating in the Nurses' Health Study (NHS) and the Nurses' Health Study II (NHS II) to explore whether asthma is associated with breast cancer. We used Cox proportional hazards models to link physician‐diagnosed asthma with subsequent incidence of breast cancer. Results Across the two cohorts, we identified 18,403 cases of physician‐diagnosed asthma. During 4,393,760 person‐years of follow‐up, 11,096 incident cases of breast cancer were diagnosed. In NHS, women with asthma had a covariate‐adjusted hazard ratio of 0.92 (95% CI: 0.86–0.99) to develop breast cancer compared to women without asthma; the respective HR in NHS II was 0.93 (0.84–1.03), and 0.92 (0.87–0.98) in the pooled analysis. Among never‐smokers, the HR for breast cancer was 0.91 (0.81–1.02) in NHS, 0.81 (0.70–0.93) in NHS II, and 0.86 (0.77–0.97) combined. In two large prospective cohorts of women, participants with asthma had a somewhat lower risk of breast cancer. An active immune system may provide protection from breast cancer. Conclusions In these longitudinal studies, women with asthma had a somewhat lower risk of breast cancer. This association was most pronounced among never smokers. An active immune system may provide protection from breast cancer.